Thermal energy storage by phase change materials in power generation - Qin, Zhen (2017)
Thermal energy storage (TES) is seen as a feasible solution to the energy crisis in the 21st century. This study focuses on the development of a TES unit with PCMs employed in a power cogeneration cycle. Firstly, the thermal analysis of some suitable PCMs was conducted through the differential scanning calorimetry (DSC) technique and the T-history method. Some disagreement was found between their measurement results and the possible reasons were discussed. Besides, it was found that eutectic salts or salts were suitable PCMs to be applied in the temperature range of 200~300 ºC. Secondly, one TES unit with paraffin wax as the PCM was constructed and tested in the laboratory. Three groups of the fan speeds and two groups of the heater power were set and the temperature of the PCM was observed in the two chambers B and D. It was found that at the lower fan speed and the higher heater power working conditions, the PCM would melt faster, and thus achieve a higher TES performance. Thirdly, the Two-D and Three-D time-dependent numerical simulations of the TES unit were conducted in COMSOL Multiphysics. The Three-D simulation counted in the natural convection inside the liquid PCM and was found closer to the experiments. The “sudden jump” of temperature at the end of the PCM melting was successfully simulated. Lastly, a TES unit final design was given and one design with selected parameters was built in COMSOL and numerically simulated. The effects of the gas and oil inlet mass flow rates were evaluated. It was found that the gas inlet mass flow rate has a higher influence on the PCM melting fraction in the steady working condition. In the future work, a more detailed numerical analysis will be done on the aspects of the melting time, the instantaneous heat transfer rate and the charging time needed based on a series of time-dependent studies. The PCM conductivity enhancement ways such as adding fins will also be considered in the investigation.